MEKANISME PENANGANAN KEJAHATAN INSIDER TRADING PASAR MODAL DI INDONESIA - Prawitra Thalib (Yuridika, 2012)
Insider trading is one of a crime that has a systemic impact and it’s difficult to prove. An abstractness of its action makes it hard to prove. Also, the impact has tremendous effect to the stock exchange in the stock market, an unhealthy condition of the stock exchange is very dangerous because it can make disbelief from the stakeholders which automatically will effect on investment in some countries. Therefore, effective handling is needed to take action against insider trading.Keywords : Insider Trading, Stakholder, Invesment